THE (UN) SPECTACULER ETHICS FOR THE ACCOUNTANT: THE HOLY QUR'AN AS A GUIDELINES, "TUNJUK AJAR MELAYU" ANSWERED - Andi Irfan (Islam Futura, 2019)
The postmodern world is a reality that is beginning to have a powerful influence in our lives today. Postmodern thoughts create a pessimistic attitude and uncare about life. Ethics thoughts developed include classic ethical streams derived from Greek philosophers' thought, contemporary ethics from medieval European thinkers until the 20th century, as well as the ethical flow of Islamic religious thought which always refers to the Holy Qur'an and As-Sunnah. Bauman (1993) offers morality without code of conduct by restoring morals to the rights and dignity of human beings. The view of Bauman (1993), universality in postmodern perspective is concerned only with the problem of globalization relating to information, technology and economics rather than ecumenical politics, culture and moral authority. Malay ethics forms a personal character and a positive characteristic of Malay people. It becomes very important to create attitudes, behaviors, ethos, and habits that focus on positive work values. The ethics of the profession which is guided by the accountant must be mirrored and follow in the footsteps of the prophet Muhammad SAW who can always be trusted by his people and business partners.